2013
DOI: 10.3944/aott.2013.3114
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficiency of different antibiotic irrigation solutions in decontamination of allografts contaminated with Staphylococcus aureus

Abstract: Rifampicin irrigation solution was the most effective in the decontamination of allografts previously contaminated with Staphylococcus aureus. Gentamicin, high-concentration fusidic acid, low-concentration fusidic and saline irrigation solutions may also be used respectively, according to their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Kaya et al[ 30 ] examined the decontaminating effects of RF, gentamicin, fusidic acid, and salinecontaining irrigation solutions on bone allografts contaminated with S. aureus and reported that the RF-containing solution exhibited the highest level of effectiveness. Apart from their beneficial impact on decontamination, there are concerns regarding the potential effects of antibiotics on wound and bone healing in orthopedic surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Kaya et al[ 30 ] examined the decontaminating effects of RF, gentamicin, fusidic acid, and salinecontaining irrigation solutions on bone allografts contaminated with S. aureus and reported that the RF-containing solution exhibited the highest level of effectiveness. Apart from their beneficial impact on decontamination, there are concerns regarding the potential effects of antibiotics on wound and bone healing in orthopedic surgeries.…”
Section: Discussionmentioning
confidence: 99%